Customer Engagement as a Mediator of Brand Trust and Customer Loyalty: Does It Work? - Rahmayani Rahmayani; Wan Suryani (Inisiatif Masyarakat Jurnal Indonesia (IMAJI), 2025)
This study aims to determine and analyze the effect of perceived value and brand trust on customer loyalty through customer engagement as a mediator variable. The sample in this study used the Slovin formula, totaling 93 respondents who were IndiHome customers in Medan Sunggal District, Medan, Indonesia, and we used structural equation modeling (SEM). The study results show that perceived value, brand trust, and customer engagement directly affect customer loyalty, and indirectly, perceived value has a non-significant effect on customer loyalty through customer engagement. In contrast, brand trust indirectly has a significant impact on customer loyalty through customer engagement.